Does Screening for Pain Correspond to High Quality Care for Veterans? - Zubkoff, Lisa (Springer-Verlag, 2010)
BACKGROUND: Routine numeric screening for pain is widely recommended, but its association with overall quality of pain care is unclear. OBJECTIVE: To assess adherence to measures of pain management quality and identify associated patient and provider factors. DESIGN: A cross-sectional visit-based study. PARTICIPANTS: One hundred and forty adult VA outpatient primary care clinic patients reporting a numeric rating scale (NRS) of moderate to severe pain (four or more on a zero to ten scale). Seventy-seven providers completed a baseline survey regarding general pain management attitudes and a post-visit survey regarding management of 112 participating patients. MEASUREMENT AND MAIN RESULTS: We used chart review to determine adherence to four validated process quality indicators (QIs) including noting pain presence, pain character, and pain control, and intensifying pharmacological intervention. The average NRS was 6.7. Seventy-three percent of charts noted the presence of pain, 13.9% the character, 23.6% the degree of control, and 15.3% increased pain medication prescription. Charts were more likely to include documentation of pain presence if providers agreed that “patients want me to ask about pain” and “pain can have negative consequences on patient’s functioning”. Charts were more likely to document character of pain if providers agreed that “patients are able to rate their pain”. Patients with musculoskeletal pain were less likely to have chart documentation of character of pain. CONCLUSIONS: Despite routine pain screening in VA, providers seldom documented elements considered important to evaluation and treatment of pain. Improving pain care may require attention to all aspects of pain management, not just screening.